2018
DOI: 10.1097/wnr.0000000000000948
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of myeloperoxidase by N-acetyl lysyltyrosylcysteine amide reduces experimental autoimmune encephalomyelitis-induced injury and promotes oligodendrocyte regeneration and neurogenesis in a murine model of progressive multiple sclerosis

Abstract: It is known that oxidative stress produced by proinflammatory myeloid cells plays an important role in demyelination and neuronal injury in progressive multiple sclerosis (MS). Myeloperoxidase (MPO) is a pro-oxidative enzyme released from myeloid cells during inflammation. It has been shown that MPO-dependent oxidative stress plays important roles in inducing tissue injury in many inflammatory diseases. In this report, we treated NOD experimental autoimmune encephalomyelitis (EAE) mice, a murine model of progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 25 publications
2
33
0
Order By: Relevance
“…41 However, when mice were followed for up to several months longer it was reported that disease might become chronically progressive as animals accumulate disability. 47 However, with the urgent unmet clinical need to develop treatment options for advanced MS, MOG induced EAE has become used as a "progressive EAE" model that purportedly resembles secondary progressive MS. 24,25,48 This clinical progression appears to begin from about day 20 after immunization when it is used to test therapeutics for use in progressive MS. [24][25][26][27][28][29][30][31] However, through literature review and as shown here, the same clinical course has been reported to be a form of chronic relapsing EAE. 23,[48][49][50] At the cellular level, CD4 T cells from MOG T-cell receptor (TCR MOG )-specific transgenic NOD mice, that select CD4 and CD8 T cells, induce a phenotypic progressive disease in NOD.Scid mice, similar to that reported using MOG immunized wild-type NOD mice.…”
Section: Discussionsupporting
confidence: 66%
See 4 more Smart Citations
“…41 However, when mice were followed for up to several months longer it was reported that disease might become chronically progressive as animals accumulate disability. 47 However, with the urgent unmet clinical need to develop treatment options for advanced MS, MOG induced EAE has become used as a "progressive EAE" model that purportedly resembles secondary progressive MS. 24,25,48 This clinical progression appears to begin from about day 20 after immunization when it is used to test therapeutics for use in progressive MS. [24][25][26][27][28][29][30][31] However, through literature review and as shown here, the same clinical course has been reported to be a form of chronic relapsing EAE. 23,[48][49][50] At the cellular level, CD4 T cells from MOG T-cell receptor (TCR MOG )-specific transgenic NOD mice, that select CD4 and CD8 T cells, induce a phenotypic progressive disease in NOD.Scid mice, similar to that reported using MOG immunized wild-type NOD mice.…”
Section: Discussionsupporting
confidence: 66%
“…22 This is consistent with other mouse strains that demonstrate a dynamic degree of adaptive immune cells infiltration as clinical disease develops and wanes. 22,36 Glial cell inflammation is thought to be part of the substrate for slow progressive nerve loss in MS. 11 However, the loss of axons and myelin, accumulation of microglial activation and gliosis reported in progressive EAE models, [24][25][26][27][28][29][30][31] is not qualitatively different from that found following the accumulation of disability from relapsing EAE in mice. 20,36 This perhaps is not surprising as monophasic or relapsing inflammatory disease activity probably creates and conditions the neurodegenerative environment that leads to the slow loss nerve loss, which does not respond rapidly to agents that target relapsing disease.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations